TINGKAT KEPUASAN PENUMPANG TERHADAP KINERJA PELAYANAN BANDARA SULTAN ISKANDAR MUDA BANDA ACEH MENGGUNAKAN METODE CUSTOMER SATISFACTION INDEX (CSI) - mutiawati, cut; Lulusi, Lulusi; Lestari, Suci (JURNAL TEKNIK SIPIL, 2021)
Sultan Iskandar Muda Airport (SIM) is located in Aceh Besar District, Aceh Province. It is crucial to analyze Airport service quality analyzed to evaluate the level of passenger satisfaction. This study aimed to evaluate the level of passenger satisfaction using the Customer Satisfaction Index (CSI) method. Data collection was conducted by administering online questionnaires to respondents who have used airport facilities. The measurement employed the Likert scale. The results showed that the most dominant characteristics of respondents were 18-27 years old (64%), male (52%), and the latest educational level of senior high school or equivalent (46.5%) and students (60.6%). The results showed that passenger satisfaction level was 75% (less satisfied) based on the 23 indicators of service performance. This finding indicates that Sultan Iskandar Muda Airport has not provided satisfactory service to passengers. The CSI scores for safety and security variables, reliability, comfort, improvement, and equality, were 74%, 76%, 78%, 74%, and 70%. The lowest assessment was on the equality variable. Thus, the capacity and quality of facilities for disabilities and nursery rooms need to be improved.